Age-related decline in endurance running performance - an example of a multiple World records holder - Lepers, R.; Cattagni, T. (Applied Physiology, Nutrition, and Metabolism, 2018)
This study examined the age-related decline in endurance running performance of one of the greatest master runners ever, Ed Whitlock, who died recently. His running performances from 1500 m to marathon were analyzed for 5 periods of 5 years from 65-69 years to 85-89 years. Despite exceptional running performances for his advanced age, the rate of decline in his performances increased after 80 years and was drastically amplified after 85 years.